A wake-up call: Information contagion and strategic uncertainty - Toni Ahnert; Christoph Bertsch (Sveriges Riksbank, 2013)
A successful speculative attack against one currency is a wake-up call for speculators elsewhere. Currency speculators have an incentive to acquire costly information about exposures across countries to infer whether their monetary authority's ability to defend its currency is weakened. Information acquisition per se increases the likelihood of speculative currency attacks via heightened strategic uncertainty among speculators. Contagion occurs even if speculators learn that there is no exposure. Our new contagion mechanism offers a compelling explanation for the 1997 Asian currency crisis and the 1998 Russian crisis, both of which spread across countries with seemingly unrelated fundamentals and limited interconnectedness. The proposed contagion mechanism applies generally in global coordination games and can also be applied to bank runs, sovereign debt crises, and political regime change.
Keywords: C7; D82; F31; G01; 330; contagion; coordination failure; global games; information acquisition